Support provided by healthcare professionals to the mothers of newborns in the neonatal unit - Suziane de Souza Giroux; Brenda Tuany Pacheco Dias; Emanuele Rocha da Silva; Jéssica Haline Souza dos Reis; Samuel Filipe Lopes Alves; Katiane da Costa Cunha; Aurimery Gomes Chermont (Hospital de Clínicas de Itajubá, 2021)
Objective: To evaluate the support offered by health professionals to mothers of newborns admitted to the neonatal unit.Methods: Descriptive cross-sectional study with a quantitative approach conducted at the Regional Hospital of Tucuruí, in the state of Pará, region of the Brazilian Amazon, where 33 mothers who had newborn children admitted to the neonatal unit responded to the structured adapted version of the NPST (Nurse Parent Support Tool ). Results: Most were aged 20-34 years (48%), married or in a stable relationship (69%), multiracial (87%), housewife (57%), with up to 11 years of study (72%). The scores for the NPST subdomains were 3.39 ± 1.65 (Communication and Information Support), 4.13 ± 1.33 (Emotional Support), 3.93 ± 1.46 (Incentive Support), and 4.21 ± 1,27 (Instrumental Support). The findings revealed unsatisfactory communication and information support from health professionals to mothers, although they expressed satisfaction with the care provided. Conclusions: The perception of scarcity of human resources and health education, verified in this study, weakens the communication process during hospitalization and influences the mother's well-being, leading to a decrease in the efficiency of the support provided. The improvement in this area can lead to better results in daily practice. The replication of this study to other locations can lead to more significant assistance to mothers of hospitalized neonates and provide new technologies and strategies in health education.